Evaluation of different techniques for percutaneous needle biopsy of synovial membrane in the dog - Siegfried, R.; Busato, A.; Schawalder, P.; Rytz, U. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Four different needles were evaluated for percutaneous needle biopsy (PNB) of the synovial membrane (SM) in six different joints (carpus, tarsus, elbow, shoulder, stifle, hip) from eight dog cadavers. Needle biopsies were retrieved with the Parker-Pearson (PP), a novel modified Parker-Pearson (PPM), the Tru-Cut (TC), and the Franklin-Silverman (FS) needles. The success rate of PNB to produce biopsies, of adequate histological quality, was assessed for each needle type and joint. The joints were subsequently surgically opened and standard open SM biopsies were harvested from an adjacent area. The articular cartilage was inspected and graded for damage caused by PNB sampling. The length of the intact synovial lining cell layer (SLCL) and the histological quality of the needle biopsies were compared to the open surgical biopsies. Success rates for the different needles were 49.2% (PPM), 37.5% (PP), 26.7% (TC), and 1.7% (FS). The highest success rates were achieved in the carpus and stifle; the lowest success rate was found in the hip joint. The intact SLCL from the PNB samples was an average of 3.4 times shorter than that of the surgical biopsies. The proportion of the samples with adequate histological quality was 81% for open surgical biopsies and 62% for PNB samples. The FS was found to produce the highest incidence of articular cartilage damage. The application of PNB for SM sampling is a valuable alternative to the open surgical biopsy in dogs. Modifications of the Parker Pearson needle by Arassy and Schumacher and novel modifications introduced by the authors, offer encouraging results, and merit further clinical and research investigations.
Keywords: Synovial membrane; percutaneous needle biopsy; joint disease; arthritis diagnosis; dog